Distribution of congenital anomalies in a neonatal intensive care unit in Turkey. (July 2014) - Dursun, Arzu; Zenciroglu, Ayşegul; Hakan, Nilay; Karadag, Nilgun; Karagol, Belma Saygili; Aydin, Banu; Dilli, Dilek; Okumus, Nurullah; Beken, Serdar
Abstract Background: Congenital anomalies are one of the important reasons of mortality and morbidity in newborns. The aim of this study is to determine the incidence, distribution and the mortality of the congenital anomalies in a single neonatal intensive care unit (NICU) from Turkey. Method: A retrospective analysis was performed between 2005 and 2012 in NICU using a computerized database. Variables including the type of anomaly, antenatal and postnatal history, gestational age, birth weight, consanguinity and other demographic, clinical and related laboratory variables were extracted from the computerized database using ICD-10 codes. Congenital anomalies were classified according to involved organ systems and also classified as single and multiple anomalies. Results: A total of 1024 newborns with congenital anomaly (CA) (13.7%) were identified among the 7450 hospitalized newborns in NICU. The most affected system was the cardiovascular system (68.8%). Most of the anomalies (67.1%) were single anomalies. Of all, 59.4% had single major, 7.7% had single minor, 9% had single major plus single minor, 18.4% had multiple major and 2% had multiple minor anomalies. On the other hand, 96.3, 1.9, 0.1 and 1.7% of the newborns had malformation, deformation, disruption and dysplasia, respectively. Chromosomal analysis was only performed 24.8% of the newborns with CA and among them, 65.3% of these were in normal limits. The most frequently detected chromosomal abnormality was trisomy 21. Overall, mortality rate was 15.5% among the newborns with CA. Conclusion: In conclusion, the most common and mortal CA was cardio-vascular malformations in our hospital. The overall prevalence of cardio-vascular malformations among the newborn was higher than previously reported studies in Turkey. Further, studies with larger sample size are needed to determine CA in Turkey.